Time Budget Pressure and Individual Factors as Triggers of Dysfunctional Audit Behavior in Government Auditors - Andre, Michael; Mutmainah, Siti (E-Jurnal Akuntansi; Vol 35 No 6 (2025)DO - 10.24843/EJA.2025.v35.i06.p05, 2025)
The suboptimal role of Indonesia's Government Internal Control System in enhancing state financial accountability has prompted this study to analyze factors influencing dysfunctional audit behavior among government auditors. This quantitative research utilized data from 100 respondents collected through questionnaires and analyzed using PLS-SEM. The findings reveal that: (1) time budget pressure increases dysfunctional behavior; (2) independence and religiosity decrease dysfunctional audit behavior; (3) male auditors demonstrate a higher propensity for dysfunctional audit behavior; and (4) professional competence shows no effect. These results underscore the importance of workload management, strengthened independence, and integration of ethical-religious values in preventing dysfunctional audit practices. Keywords: Dysfunctional; Audit; Religiosity; Gender.